1986
DOI: 10.1247/csf.11.181
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol ester-induced regulation of transferrin receptors in human leukemia K562 cells.

Abstract: ABSTRACT. The treatment of human leukemia K562 cells with 12-0-tetradecanoyl phorbol-13-acetate (TPA) caused a decrease of transferrin receptors. The mechanism of the decrease of the receptors with TPA has been investigated. In cells incubated with TPA, the rate of biosynthesis of transferrin receptors was reduced to 10-20 % of that in untreated cells. Pulsechase experiments showed that turnover of the receptors in TPA-treated cells was accelerated over that in untreated cells. These results indicated that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Finally, enhanced uptake of Tf in response to DAG (or phorbol ester) treatment is unique to trypanosomatids. In human cells, PMA treatment does not increase endocytosis of Tf [53], [54]. During a trypanosome infection of vertebrates, the parasite competes with host cells for Tf in host blood.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, enhanced uptake of Tf in response to DAG (or phorbol ester) treatment is unique to trypanosomatids. In human cells, PMA treatment does not increase endocytosis of Tf [53], [54]. During a trypanosome infection of vertebrates, the parasite competes with host cells for Tf in host blood.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we reported diminished biosynthesis of transferrin receptor in K562 cells treated with phorbol ester (Kohno et al 1986). In all of these cases, down-regulation of transferrin receptors was observed.…”
Section: Discussionmentioning
confidence: 81%
“…In addition, we have previously shown that the decrease in transferrin receptor expression in phorbol ester-treated K562 cells is attributable in part to a reduction in biosynthesis of the receptors (Kohno et al 1986). We therefore attempted to establish whether or not the reduction of transferrin receptor expression by lead treatment was due to a decrease in the receptor biosynthesis.…”
Section: Effect Of Lead On Biosynthesis Of Transferrin Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phorbol esters are mitogenic for human blood lymphcoytes and induce differentiation of T and B cells, they can also modu late cell-mediated cytotoxicity and antibody produc tion. In macrophages, phorbol esters induce DNA synthesis and phagocytosis, and human promyelocytic leukemia cells mature to macrophages when treated with these compounds [5][6][7][8], Phorbol esters enhance transferrin endocytosis and iron uptake by immature erythroid cells [9], they also influence trans ferrin receptors in human leukemic cells [10]. Results of numerous studies suggested that phorbol esters arc able to stimulate human and animal granulocytemacrophage [GM] progenitor cells in long-term cul ture of bone marrow [11][12][13][14][15], It is now widely believed that the microenviron ment created in bone marrow by stromal cells plays a very important role in such processes as self-regenera tion, differentiation and maturation of progenitor cells during hematopoiesis.…”
Section: Introductionmentioning
confidence: 99%